Analysis of Correctional Policy in Reducing the Impact of Overcapacity at Banceuy Prison from Human Rights Perspective - Lesmana, Deni Angki; Karnado, Gustira; Fikri, Ahmad Ma’mun (LifeSciFi, 2025)
Overcrowding at the Class IIA Banceuy Prison has resulted in serious violations of inmates’ human rights, including the rights to health, security, and a decent standard of living. This study aims to analyze the effectiveness of human rights-based correctional policies, such as assimilation programs, parole, and restorative justice, in responding to the impacts of overcrowding. Using a normative juridical approach and field data through observation and interviews, the study results indicate that these policies have had a positive impact, but their implementation remains hampered by complex administrative procedures, limited facilities, and a shortage of teachers and supervisors. Skills training programs have proven beneficial, but access remains limited. Collaboration with NGOs has helped provide counseling and health services, although they are not evenly distributed. This study recommends simplifying administrative procedures, increasing the budget for basic facilities, and expanding cross-sectoral collaboration, including with the business world and educational institutions. Furthermore, reform of penal policy through decriminalization and the widespread implementation of restorative justice is considered crucial to reducing the burden on prisons. The implications of this research underscore the need for a more humane, inclusive, and rights-oriented correctional approach to prisoners.